2009
DOI: 10.1007/s00330-009-1537-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of percutaneous resection and interstitial laser ablation of osteoid osteomas

Abstract: To evaluate the efficiency and complication rate of two percutaneous treatments of osteoid osteomas, percutaneous trephine resection (PR) and interstitial laser ablation (ILA). Ethical review board was obtained for the retrospective study. One hundred and 26 patients were treated by PR (n = 26) or ILA (n = 100) under CT, with a median follow-up of 113 months for the PR group and 47 months for the ILA group. In the group treated by PR, the clinical success rate was 96% at 6-month and 95% at 24-month follow-up, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…Several percutaneous minimally invasive techniques have been used for destruction of the nidus of osteoid osteomas such as trephine, laser and radiofrequency ablation [6,8,[10][11][12][13][14][15][16][17]. Radiofrequency ablation (RFA) is a form of electrosurgery in which an alternating current of high-frequency radiowaves (>10 kHz) flows from a radiofrequency (RF) generator through an electrode tip and dissipates its energy as heat [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several percutaneous minimally invasive techniques have been used for destruction of the nidus of osteoid osteomas such as trephine, laser and radiofrequency ablation [6,8,[10][11][12][13][14][15][16][17]. Radiofrequency ablation (RFA) is a form of electrosurgery in which an alternating current of high-frequency radiowaves (>10 kHz) flows from a radiofrequency (RF) generator through an electrode tip and dissipates its energy as heat [18].…”
Section: Introductionmentioning
confidence: 99%
“…Rosenthal et al [11] reported recurrence in 7/74 femoral osteoid osteomas, while Hoffman et al did not report any. Results have also been shown to be good with laser ablation (Gangi et al [17] and Roqueplan et al [18], 99 and 96% of good results respectively), in particular in relation to the risk of postoperative fracture, which seems to be nearly inexistent, even with full weight-bearing after surgery. Nevertheless, these authors reported numerous minor potential complications, that are not found with the PBRD procedure: nerve injury and tendinitis (Roqueplan et al [18]), skin burns and broken material (Étienne et al [19]).…”
Section: Discussionmentioning
confidence: 90%
“…The frequency of this entity confirms the need for this study. Many of the studies of percutaneous treatment, either by drilling [7][8][9][10] or thermoablation [11][12][13][14][15][16][17][18][19], have not differentiated between the femoral neck and other locations in the reported cases. The advantage of our series is that it specifically focuses upon this location.…”
Section: Discussionmentioning
confidence: 95%
“…However, our study showed that, independent of the location of the OO within the bone, the nidus mineralization ratio of OOs increases significantly with the duration of symptoms and may therefore represent a marker of tumor In our study, we provide objective arguments to evaluate the age of an OO on the basis of the nidus mineralization ratio. It may represent a key finding in the selection of interventional or conservative treatment in cases of OOs with critical locations (spine and limb extremities), when structures such as nerves are at risk or when skin complications are considered, despite thermal protection techniques known to make the procedure secure (30)(31)(32)(33). The nidus mineralization ratio may also be useful in monitoring the lesion, in case the patient declines the percutaneous treatment.…”
Section: Discussionmentioning
confidence: 97%